2004
DOI: 10.1021/bi0358869
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric Measurement of Phospholipid Interaction with Methyl-β-Cyclodextrin

Abstract: Cyclodextrins are able to bind hydrophobic molecules in their interior cavity and as such have received a great deal of attention as carriers of cholesterol, lipophilic drugs, and other sparingly soluble compounds. Despite the importance of these biochemical applications, relatively little is known about the interactions of cyclodextrins with phospholipid membranes. Here we characterize the binding of randomly methylated β-cyclodextrin (mβCD) to 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) using rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
105
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(129 citation statements)
references
References 34 publications
23
105
1
Order By: Relevance
“…Void volume fractions contained the lipid vesicles (SUVs and residual MLVs) (not shown). To incorporate cholesterol the exchange vesicles were then incubated with CLC using a lower M␤CD concentration (generally 2.5 mM for PC SUVs and 7.5 mM for POPE:POPS SUVs) so that the M␤CD would not bind phospholipid (43). In the final step, the cholesterol-containing asymmetric SUVs were separated from other components on a Sepharose CL-4B column.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Void volume fractions contained the lipid vesicles (SUVs and residual MLVs) (not shown). To incorporate cholesterol the exchange vesicles were then incubated with CLC using a lower M␤CD concentration (generally 2.5 mM for PC SUVs and 7.5 mM for POPE:POPS SUVs) so that the M␤CD would not bind phospholipid (43). In the final step, the cholesterol-containing asymmetric SUVs were separated from other components on a Sepharose CL-4B column.…”
Section: Resultsmentioning
confidence: 99%
“…It works with many different lipids and can be used at elevated temperatures that might aid exchange for lipids with high T m values. Introduction of cholesterol without disruption of the vesicles is possible because cholesterol-M␤CD complexes can be prepared at M␤CD concentrations too low to bind phospholipids (43) and is no doubt aided by rapid cholesterol equilibration between the inner and outer leaflets (69). Although the final cholesterol concentration in the inner and outer leaflets is unknown, the need to maintain mass balance between the leaflets requires a similar final mole fraction of cholesterol in the two leaflets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by another group demonstrated that a phosphatidylcholine carrying a palmitic acid molecule and an oleic acid molecule (POPC) binds the four molecules of methyl-␤-cyclodextrin (M␤CD, but not dM␤CD) and has further suggested that each fatty acid chain of the POPC molecule is embedded inside the ring structure of one or two molecules of M␤CD (2). No earlier investigations, however, have revealed the molecular interaction between ␤CDs (including M␤CD and dM␤CD) and other glycerophospholipids, such as PE and PG-CL.…”
Section: Discussionmentioning
confidence: 99%
“…M␤CD, a water-soluble cyclic oligosaccharide, has a high affinity for cholesterol and has been extensively used as an effective tool for the transport of cholesterol away from cell surfaces (33). M␤CD incubations selectively remove cholesterol from cell membranes while not affecting membrane integrity when concentrations do not exceed 15 mM (34,35). After the incubation period, cells were washed with PBS once and the media was changed.…”
Section: Membrane Cholesterol Depletion and Enrichment Of Hek 293mentioning
confidence: 99%